2021
DOI: 10.1186/s40794-021-00156-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Schistosoma mansoni infection among children in Ethiopia: a systematic review and meta-analysis

Abstract: Background Schistosomiasis is a neglected tropical disease caused by mainly Schistosoma mansoni and Schistosoma hematobium. The disease is very common in Africa including Ethiopia. Schistosoma mansoni is a major public health problem in Ethiopia especially among children. This review is aimed to indicate the prevalence of Schistosoma mansoni among children at the national and regional levels. Methods and material The PRISMA guidelines were followed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…A systematic review and meta-analysis reported 18.7% (95%CI: 14.7–23.5) pooled prevalence of S . mansoni infection in Ethiopian general population and 37.13% (95%CI: 30.02–44.24) among children [ 21 , 22 ]. A study conducted in Northwest Ethiopia reported significantly lower mean values of Hgb, RBC, MCHC, total protein (TP), total cholesterol (TC), and total WBC count among S .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis reported 18.7% (95%CI: 14.7–23.5) pooled prevalence of S . mansoni infection in Ethiopian general population and 37.13% (95%CI: 30.02–44.24) among children [ 21 , 22 ]. A study conducted in Northwest Ethiopia reported significantly lower mean values of Hgb, RBC, MCHC, total protein (TP), total cholesterol (TC), and total WBC count among S .…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, schistosomiasis is a major public health problem with more than 5 million people infected and more than 37 million people at risk of infection [20]. A systematic review and meta-analysis reported 18.7% (95%CI: 14.7-23.5) pooled prevalence of S. mansoni infection in Ethiopian general population and 37.13% (95%CI: 30.02-44.24) among children [21,22]. A study conducted in Northwest Ethiopia reported significantly lower mean values of Hgb, RBC, MCHC, total protein (TP), total cholesterol (TC), and total WBC count among S. mansoni infected patients compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…We identi ed 31 articles that report the burden of prioritized NTDs in Ethiopia (3, 9, 26-35, 11, 36-45, 19, 46, 20-25). Most were systematic reviews and metaanalyses on trachoma (19), leishmaniasis (20)(21)(22)(23)(24), soil transmitted helminthiasis (STH) (25)(26)(27)(28)(29), schistosomiasis (29)(30)(31)(32), scabies (33); LF and podoconiosis (34)(35)(36)(37), review on onchocerciasis (39), and historical review of NTDs in Ethiopia (1941-2019) (38). Trachoma, podoconiosis and leishmaniasis are three common NTDs in Ethiopia (3,11).…”
Section: Evidence On Burden Of Ntds In Ethiopiamentioning
confidence: 99%
“…Overall, the prevalence of schistosomiasis varies across regions of Ethiopia from 39.8-41.5% in SNNP (30,31), 41% in Amhara. 31.4% in Tigray, 28.9% in Oromia (31), and 15% in Afar region (30).…”
Section: Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation